Polyphenol-Rich Extract of Syzygium cumini Leaf Dually Improves Peripheral Insulin Sensitivity and Pancreatic Islet Function in Monosodium L-Glutamate-Induced Obese Rats - Sanches, Jonas R.; França, Lucas M.; Chagas, Vinicyus T.; Gaspar, Renato S.; dos Santos, Kayque A.; Gonçalves, Luciana M.; Sloboda, Deborah M.; Holloway, Alison C.; Dutra, Richard P.; Carneiro, Everardo M.; Cappelli, Ana Paula G.; Paes, Antonio Marcus de A. (Frontiers in Pharmacology, 2016)
Syzygium cumini (L.) Skeels (Myrtaceae) has been traditionally used to treat a number of illnesses. Ethnopharmacological studies have particularly addressed antidiabetic and metabolic-related effects of extracts prepared from its different parts, especially seed and pulp-fruit, however there is a lack of studies on phytochemical profile and biological properties of its leaf. As there is considerable interest in bioactive compounds to treat metabolic syndrome and its clustered risk factors, we sought to characterize the metabolic effects of hydroethanolic extract of S. cumini leaf (HESc) on lean and monosodium L-glutamate (MSG)-induced obese rats. HPLC-MS/MS characterization of the HESc polyphenolic profile, at 254 nm, identified 15 compounds pertaining to hydrolysable tannin and flavanol subclasses. At 60 days of age, both groups were randomly assigned to receive HESc (500 mg/kg) or vehicle for 30 days. At the end of treatment, obese+HESc exhibited significantly lower body weight gain, body mass index, and white adipose tissue mass, compared to obese rats receiving vehicle. Obese rats treated with HESc showed a 2-fold increase in lipolytic activity in the periepididymal fat pad, as well as, brought triglyceride levels in serum, liver and skeletal muscle back to levels close those found in lean animals. Furthermore, HESc also improved hyperinsulinemia and insulin resistance in obese+HESc rats, which resulted in partial reversal of glucose intolerance, as compared to obese rats. HESc had no effect in lean rats. Assessment of ex vivo glucose-stimulated insulin secretion showed HESc potentiated pancreatic function in islets isolated from both lean and obese rats treated with HESc. In addition, HESc (10 – 1000 ug/mL) increased glucose stimulated insulin secretion from both isolated rat islets and INS-1E beta cells. These data demonstrate that S. cumini leaf improved peripheral insulin sensitivity via stimulating/modulating beta cell insulin release, which was associated with improvements in metabolic outcomes in MSG-induced obese rats.